The coronary artery disease‐associated gene C6ORF105 is expressed in human macrophages under the transcriptional control of PPARγ. Issue 4 (14th January 2015) - Chinetti-Gbaguidi, G.; Copin, C.; Derudas, B.; Vanhoutte, J.; Zawadzki, C.; Jude, B.; Haulon, S.; Pattou, F.; Marx, N.; Staels, B.
Abstract : Coronary artery disease (CAD) is a major cause of morbidity and mortality. Mutations in C6ORF105, associated with decreased gene expression, positively correlate with the risk of CAD in Chinese populations. Moreover, the C6ORF105‐encoded protein may play a role in coagulation. Here, we report that C6ORF105 gene expression is lower in circulating mononuclear cells from obese diabetic than lean subjects. Moreover, C6ORF105 is expressed in human macrophages and atherosclerotic lesions, where its expression positively correlates with expression of the transcription factor Peroxisome Proliferator‐Activated Receptor (PPAR)γ. Activation of PPARγ increases, in a PPARγ‐dependent manner, the expression of C6ORF105 in human macrophages and atherosclerotic lesions. Abstract : C6ORF105 is expressed in human macrophages in vitro . C6ORF105 is expressed in macrophages resident in human atherosclerotic lesions. In human atherosclerotic lesions, C6ORF105 positively correlates with PPARγ. Expression of C6ORF105 is induced by PPARγ activation in human macrophages.